2020
DOI: 10.21203/rs.2.11628/v5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Level of awareness of Saudi medical students of the internet-based health-related information seeking and developing to support health services

Abstract: Background. Many studies are available in the literature about e-health in Saudi Arabia, however, data is limited to a few organizations and does not necessarily reflect the current and potential use of e-health for health care organizations in the country. This study aimed to determine the level of awareness of Saudi medical students of the internet-based health-related information seeking and developing to support health services and significant predictors of their practice.Methods. A cross-sectional survey … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…Our finding implied healthcare providers who had good awareness were more likely to be ready. This finding was consistent with previous research findings [ 78 , 79 ]. This implied that awareness campaigns enabled individuals to understand the values of EHRs and to take action.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our finding implied healthcare providers who had good awareness were more likely to be ready. This finding was consistent with previous research findings [ 78 , 79 ]. This implied that awareness campaigns enabled individuals to understand the values of EHRs and to take action.…”
Section: Discussionsupporting
confidence: 94%
“…Knowledge score was calculated as follows: 1 point for a correct answer and 0 points for don’t know & incorrect answer. Respondents who scored the mean and above were considered as having good knowledge, whereas those who scored below the mean were considered as having poor knowledge [ 45 , 50 , 78 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second result of this study which showed a positive significant relationship between comprehensive EMR and patient-centeredness in an advanced tertiary care setting in Saudi Arabia can be explained by the fact that the utilization of comprehensive EMR in KAMC increases the ability to focus on patients and provide care that respects and responds to the patient's preferences, needs and individual values, as it focuses on providing accurate information about the patient, whether it is personal information, information about the diagnosis of his disease, or information about the results of medical tests and examinations, or information about the treatment and its scheduled program and the extent of the patient's response to this treatment and other things that contribute to raising the efficiency of medical care, which was emphasized in the study of Kalra, Baruah and Unnikrishnan [16] and Aldosari et al [27]. Furthermore, there is a consistency between this result and the studies of Adler-Milstein et al and Aldebasi et al [34,35] which indicated that the use of comprehensive EMR is related to improving performance and increasing the ability to focus on patients, as it facilitates the process of entering patient information and helps them in improving the quality of health care service. The system also contributes to increasing the effectiveness of communications between doctors and other departments, as well as speeding up and developing procedures, and maintaining high standards in services.…”
Section: Discussionsupporting
confidence: 54%
“…The Ministry of Health (MOH) launched an E-Health strategy that depends on several dimensions such as patient-centric care and interoperable EHR [ 22 ]. A recent study found the attitude towards E-health use was positive among medical students [ 23 ]. Indeed, authentic of clinical experiences, which included documenting in patients’ records, was mentioned as a factor for improving Saudi medical students learning environment [ 24 ].…”
Section: Introductionmentioning
confidence: 99%